(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
The purpose of this study is to determine the background of martial arts of Tarung Derajat becoming an achievement sport, the efforts made to become an achievement sport, as well as the impact of martial arts of Tarung Derajat on the development of achievement sports in Indonesia. The steps taken in using this historical method are heuristics, criticism, interpretation, and historiography. The study results show that initially the martial art of Tarung Derajat was created by Achmad Dradjat to protect himself from acts of violence and to raise his honor as a victim of violence. Achmad Dradjat then declared the establishment of the Tarung Derajat academy on July 18 1972, which at that time was still called the boxer martial arts academy. As time went by, Tarung Derajat as a martial art began to transform into an achievement sport. This was marked by the inclusion of Tarung Derajat as a member of KONI on January 6 1997. As a member of KONI, tarung derajat regularly competed in the National Sports Week (PON) and was even competed in the SEA Games as an exhibition sport. To date, Tarung Derajat has contributed to the development of martial arts and sports achievements in Indonesia.